THE ROLE OF TAMAN PENDIDIKAN AL-QUR'AN AL MUTTAQIN IN ERADICATING AL-QUR'AN ILLITERACY IN DUSUN PLELEN, SIDOHARJO VILLAGE, PACITAN - Arifin, Arifin; Agustiani, Happy (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
Taman Pendidikan Al-Qur'an (TPQ) Al Muttaqin, located in Dusun Plelen, Sidoharjo Village, Pacitan, has been instrumental in addressing Al-Qur'an illiteracy among children in the area. This non-formal, non-profit institution has employed the Ummi and Iqro’ methods to teach children how to read and write the Al-Qur'an. This research aims to explore the role of TPQ Al Muttaqin in combating Al-Qur'an illiteracy, and to assess the effectiveness of the teaching methods applied. The study’s findings indicate that the TPQ program has significantly improved the Al-Qur'an literacy of its participants, with 35 out of 50 children demonstrating proficiency in reading and writing the Al-Qur'an